2003
DOI: 10.2223/jped.937
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between pre-thickened and home-thickened formulas in gastroesophageal reflux treatment

Abstract: Objective: the purpose of this study was to compare the effectiveness of a pre-thickened infant formula (Nan AR) with a conventional homemade formula in the reduction of regurgitation and vomiting in infants with gastroesophageal reflux.Methods: a hundred children, under 12 months, not exclusively breast feeding, were select for the study. Forty-eight were treated with conventional formula with starch and 52 with pre-thickened infant formula.Results: there was no statistically significant difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…General complication rates reported in studies were also summarized. Overall rate of adverse events or unspecified complications were reported in studies examining the use of locust bean gum, 35,36,42 cornstarch, 32,43 and rice starch. 29 All 6 investigations indicated that no infant experienced any complications during the study period or that the rate of adverse events was not significant.…”
Section: Clinical Questionmentioning
confidence: 99%
“…General complication rates reported in studies were also summarized. Overall rate of adverse events or unspecified complications were reported in studies examining the use of locust bean gum, 35,36,42 cornstarch, 32,43 and rice starch. 29 All 6 investigations indicated that no infant experienced any complications during the study period or that the rate of adverse events was not significant.…”
Section: Clinical Questionmentioning
confidence: 99%